Proverbs and Gender Equalities and Equities in African Cultueres: Yoruba Culture as A case Study (Global Journal of Human-Social Science, 2012)
Proverbs in Yoruba culture recognize the natural dichotomy that exists between male and female. But while it recognizes their co-existence, it as well underlines the fact that the relationship between women and men should be founded on equality. It is part of human nature to want to dominate one another. When this happens, both the oppressed and oppressor invent a proverb to back his or her position. And so while the oppressor would event one to justify his or her position, the oppressed would also think deeply and invent one that would show that the oppressor is oppressing him or her. To invent a proverb one must be intelligent and have vast human experience of sociocultural activity of his or her environment. It is not enough to be intelligent it has to be combined with age steeped in wide and vast experience. It is this that makes a good proverb stands the test of time.
Keywords: Gender Equalities and Equities; natural dichotomy